Challenging policies that prohibit public transport use: Travelling with pets as a case study. (December 2020) - Kent, Jennifer L.; Mulley, Corinne; Stevens, Nick
Abstract: Any serious challenge to car-dependency requires a better understanding of barriers to the uptake of alternative transport modes, including public transport. Such barriers will be complex and contextual. They may be major, such as the absence of a time competitive public transport option, or a collection of minor, seemingly peripheral inconsistencies between the needs of the user and the operation of the system. This paper provides a comprehensive examination of one such barrier – the restriction of pets on public transport. Typically, cities in Europe, and many in North America and the UK, permit dogs to ride public transport with their carers. Australian cities, in contrast, are more restrictive, deeming the popular practice of dog ownership in Australian cities a relatively car-dependent affair. Drawing from a survey of 1091 Sydney residents, we examine reactions to a hypothetical change in the city's pets on public transport policy to allow dogs to ride with their carers. Specifically, we examine the level of support for the policy change, explore who supports and who would be against the change, and unpick the potential impact of a policy change on user behaviour. We find a low level of opposition to policy change (23%), with only a small portion of respondents indicating that a policy to allow pets on public transport would discourage their use of public transport (21%). The key determinants of policy support relate to attitudes to dogs rather than transport related characteristics, highlighting the need for transport policy makers to look beyond transport issues when considering policy change. The paper concludes with reflections on the importance of investigating the smaller ways public transport policy might be able to encourage transition away from private car use. Highlights: Prohibitions on public transport can prevent the provision of an equitable and useful network. Pets are prohibited on public transport in some cities, deeming pet ownership a car dependent practice. Removal of this prohibition requires understanding peoples' attitudes to dogs, as well as transport. A revised pets on public transport policy should be tailored to the network.